The effect of oolong tea as an adjunct to nonsurgical management of chronic periodontitis: A randomized controlled clinical trial - Sonal Nafade; Rupali Agnihotri; Shobha Ullas Kamath; Padmaja Ananth Shenoy; Nisha Abdul Khadher; Deeksha Dayanand Nayak (Shahrekord University of Medical Sciences, 2022)
Introduction: Oolong tea, a functional food, has numerous therapeutic benefits owing to the presence of bioactive polyphenols, theasinensins (TS) and catechins. The present study aimed to evaluate the influence of systemic administration of oolong tea as an adjunct to nonsurgical periodontal therapy (NSPT) in the management of chronic periodontitis (CP).Methods: A total of 60 subjects with mild to moderate CP were randomly divided into two groups of tests (n = 30) and the controls (n = 30). They underwent NSPT with adjunctive oolong tea supplementation in the test group only. At baseline, 1, and 3 months, their gingival index (GI), plaque index (PI), probing pocket depth (PPD), clinical attachment loss (CAL), percentage of sites with bleeding on probing (BOP), and lobene stain index (LSI) were recorded. Furthermore, the levels of glutathione peroxidase (GPx), total antioxidants (TAO), and malondialdehyde (MDA) were also estimated in gingival crevicular fluid (GCF), saliva and serum. Additionally, colony-forming units (CFUs) of selective supra and subgingival plaque bacteria were estimated in the plaque samples.Results: In both groups, at 1 month, the GI, PI, BOP, GPx, and TAO levels were improved with a reduction in the levels of MDA and CFU's and no staining of teeth (P < 0.05). The results were maintained in the test group at 3-month recall visit.Conclusion: Adjunctive administration of oolong tea with NSPT reduced the local and systemic oxidative burden and rapidly resolved the inflammation in CP. This would be specifically beneficial in CP subjects with systemic conditions.